2022
DOI: 10.1371/journal.pgph.0000835
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events following COVID-19 vaccination in Kwara State, North-central Nigeria

Abstract: Safe and effective vaccination remains the mainstay of control of COVID-19 because there is still no universally recommended treatment. This strategy is however being threatened by vaccine hesitancy and resistance due to fear of adverse events and safety concerns. It is, therefore, necessary to study post-vaccination adverse events (AE) in various populations and geographical areas. The objective of this study was to analyze the adverse events following COVID-19 vaccination in five major immunization centers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
1
1
Order By: Relevance
“…A larger number of the respondents were females (70.4%), which agrees with the survey data of COVID-19 vaccine adverse events among hospital staff in a national referral hospital in Indonesia by Djanas et al (2021), where females had the highest number of participants. However, this study was contrary to the study by Odeigah et al (2022) where males accounted for 64.3%. In this study, most of the health workers (50.3%) were aged between 31 and 40.…”
Section: Discussioncontrasting
confidence: 99%
“…A larger number of the respondents were females (70.4%), which agrees with the survey data of COVID-19 vaccine adverse events among hospital staff in a national referral hospital in Indonesia by Djanas et al (2021), where females had the highest number of participants. However, this study was contrary to the study by Odeigah et al (2022) where males accounted for 64.3%. In this study, most of the health workers (50.3%) were aged between 31 and 40.…”
Section: Discussioncontrasting
confidence: 99%
“…No significant relationship was observed between age and gender and occurrence of AEs. This is similar to the finding by Odeigah et al [38] Osibogun et al in their study however observed that the older age group(>60 years) had a lower likelihood for COVID-19 Vaccine AEs compared with the 18-24 years age group [28]. In this study, there was also no significant association between the occurrence of AEs and the sociodemographic variables of respondents.…”
Section: Discussionsupporting
confidence: 91%
“…The study done in Yenogoa, South-South Nigeria revealed pain at injection site as the commonest symptom followed by headache and fatigue [35]. Previous studies also have similar findings [31][32][33][38][39][40].…”
Section: Discussionmentioning
confidence: 77%